DATA DRIVEN MANAGEMENT AND ARTIFICIAL INTELEGENCE: A SYSTEMATIC LITERATURE REVIEW ON THE TRANSFORMATION OF MANAGERIAL THINKING (Proceeding of SINERGY, 2026)
Digital transformation exerts a profound and far reaching impact across various organizational domains, encompassing work dynamics, organizational structures, and business models. It plays a pivotal role in fostering innovation and enhancing operational efficiency within organizations. This study employs a Systematic Literature Review (SLR) methodology, as it facilitates a comprehensive and systematic analysis of relevant literature. Furthermore, the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework was applied to guide the literature selection process.The findings reveal that Artificial Intelligence (AI) and Big Data have disrupted conventional managerial thinking, shifting traditional approaches toward modern, analytics-driven strategies. Evidence suggests that the implementation of AI within management significantly bolsters operational efficiency and effectiveness. Consequently, it is imperative for organizations to conduct regular audits and evaluations of their underlying algorithms. Adopting a hybrid management approach emerges as an ideal solution to navigate current challenges, ultimately enhancing organizational effectiveness and ensuring informed decision making.